Distinct Exciton Dissociation Behavior of Organolead Trihalide Perovskite and Excitonic Semiconductors Studied in the Same System. Issue 18 (15th January 2015) - Hu, Miao; Bi, Cheng; Yuan, Yongbo; Xiao, Zhengguo; Dong, Qingfeng; Shao, Yuchuan; Huang, Jinsong
<x xml:space="preserve">Abstract</x> The nonexcitonic character for organometal trihalide perovskites is demonstrated by examining the field‐dependent exciton dissociation behavior. It is found that photogenerated excitons can be effectively dissociated into free charges inside perovskite without the assistance of charge extraction layer or external field, which is a stark contrast to the charge‐separation behavior in excitonic materials in the same photovoltaic operation system.